Positive electrode binder for lithium ion batteries
By using an improved adhesive containing VDF cluster, (methyl) acrylic polymer and solvents in the Lifepo4 active material electrode, the problem of rapid viscosity and gelization in existing technologies have been solved. Adhesive and electrochemical stability.
Patent Information
- Application Number
- CN202380046213.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-12
- Filing Date
- 2023-04-11
- Publication Date
- 2025-01-21
AI Technical Summary
When used to prepare slurry to form a positive electrode with LiFePO4 active material, existing modified polar PVDF polymers tend to cause rapid increase in viscosity and form gels, resulting in the inability to effectively use the adhesive as the LPF cathode.
A positive electrode forming composition, which contains a positive electrode active material with an olive structure and an improved adhesive. The composition of objects, solvents and optional conductive additives avoids gelization through specific composition ratio and process treatment.
It is achieved to prevent gelization, while improving the adhesion and electrochemical stability of the electrode, so that the composition can be effectively used to create a positive electrode of the LI ion battery with enhanced performance.
Smart Images

Figure BDA0005180050610000031 
Figure BDA0005180050610000051 
Figure BDA0005180050610000061
Abstract
Description
[0001] Cross-Reference to Prior Applications
[0002] This application claims priority from European application number 22305526.0 filed on April 16, 2022, the entire contents of which are incorporated by reference into the present application for all purposes. Technical Field
[0003] The present invention relates to a binder for a positive electrode of a Li-ion battery, a method for preparing the electrode and the use thereof in a Li-ion battery.
[0004] The present invention also relates to a Li-ion battery manufactured by incorporating said electrode. Background Art
[0005] Electrochemical devices such as secondary batteries typically include a positive electrode, a negative electrode, and an electrolyte.
[0006] The most critical component of a lithium ion secondary battery is the positive electrode (cathode) material, the performance of which affects the overall performance of the lithium ion secondary battery. Various attempts are being made to provide cathode materials with low production costs and large energy capacity while maintaining high temperature stability.
[0007] Conventional active materials at the positive electrode are typically of the LiMO2 type, LiMPO4 type, Li2MPO3F type, Li2MSiO4 type (wherein M is Co, Ni, Mn, Fe or a combination of these), LiMn2O4 type or S8 type.
[0008] Among these materials, due to the high theoretical capacity (170 mA h g -1 ), high safety, and economic benefits, lithium iron phosphate (LiFePO4 or LFP) with an olivine structure has attracted attention as a potential cathode material for Li-ion batteries.
[0009] Electrodes for lithium batteries are typically produced by mixing a binder with powdered electrode active materials.
[0010] Fluororesins such as vinylidene fluoride-based polymers have been used as binders for forming positive electrodes. In particular, polyvinylidene fluoride (PVDF) provides good electrochemical stability and high adhesion to electrode materials and current collectors. Therefore, PVDF is a preferred binder material for electrode slurries.
[0011] US2018 / 0355206 discloses the use of a copolymer of methyl methacrylate and methacrylic acid mixed with PVDF for preparing LiNMC electrode slurries, which have good adhesion to current collectors; the viscosity of the mixture makes it easy to spread the active material on the metal current collector, thereby facilitating the manufacture of electrodes for lithium-ion batteries.
[0012] US 2015 / 0280238 discloses a stable electrode binder dispersion for preparing an LFP cathode of a lithium ion battery, the dispersion comprising PVDF and a (meth)acrylic polymer dispersant dispersed in an organic diluent.
[0013] Modified polar PVDF polymers, such as those comprising repeating units derived from hydrophilic (meth) acrylic monomers (e.g., acrylic acid), are well known in the art. Such copolymers have been developed with the aim of adding suitable adhesion to metals (e.g., aluminum or copper) to the mechanical properties and chemical inertness of PVDF.
[0014] However, modified polar PVDF polymers have a significant disadvantage when used to prepare slurries for forming positive electrodes with LiFePO4 active materials, namely that the slurries often undergo a rapid viscosity increase leading to gel formation, thus preventing these polymers from being used as binders for LPF cathodes.
[0015] The present invention provides a positive electrode forming composition including an LFP active material, which is capable of preventing gelation while being capable of producing an electrode with enhanced adhesion and electrochemical stability. Summary of the invention
[0016] The object of the present invention is therefore a positive electrode forming composition (C) comprising at least one positive electrode active material (AM) having an olivine structure and a binder (B), wherein the binder (B) comprises, preferably consists of:
[0017] a) at least one vinylidene fluoride (VDF) copolymer [polymer (F)] comprising:
[0018] (i) a repeating unit derived from VDF;
[0019] (ii) repeating units derived from at least one hydrophilic (meth)acrylic monomer (MA) having formula (I):
[0020]
[0021] in:
[0022] - R1, R2 and R3, which are the same or different from each other, are independently selected from hydrogen atoms and C1-C3 hydrocarbon groups, and
[0023] -R X It is a C1-C 20 a hydrocarbon moiety, the functional group being selected from a hydroxyl group, a carboxyl group, an epoxy group, an ester group and an ether group,
[0024] The amount of these repeating units is from 0.05% to 10% by mole relative to the total number of moles of the repeating units of polymer (F);
[0025] b) at least one (meth)acrylic polymer [polymer (A)];
[0026] c) at least one solvent (S); and
[0027] d) Optionally at least one additive imparting conductivity.
[0028] In a second example, the present invention relates to the use of an electrode forming composition (C) of the present invention in a method for producing a positive electrode [electrode (E)] of an electrochemical device, the method comprising:
[0029] (i) providing a metal substrate having at least one surface;
[0030] (ii) providing an electrode-forming composition (C) as defined above;
[0031] (iii) applying the composition (C) to at least one surface of a metal substrate, thereby providing a component comprising the metal substrate coated with the composition (C) on the at least one surface;
[0032] (iv) drying the assembly provided in step (iii).
[0033] In a third example, the invention relates to a positive electrode (E) obtainable by the process of the invention.
[0034] In a fourth embodiment, the present invention relates to an electrochemical device comprising the positive electrode (E) of the present invention. DETAILED DESCRIPTION
[0035] In the context of the present invention, the use of parentheses "(...)" before and after a symbol or a number identifying a formula or a part of a formula has the sole purpose of better distinguishing this symbol or number relative to the rest of the text; therefore, said parentheses can also be omitted.
[0036] The terms "acrylic" and "acrylate" are used interchangeably (unless doing so would change the intended meaning) and include acrylic acid and its derivatives. The terms "(meth)acrylic" or "(meth)acrylate" are intended to encompass both acrylic / acrylate and methacrylic / methacrylate forms of the indicated material, e.g., (meth)acrylate monomers.
[0037] The active material (AM) having an olivine structure is a compound having the following formula:
[0038] Li x A y D z PO4,
[0039] Wherein A is selected from the group consisting of Mn, Fe, Co, Ni and Cu; D is selected from the group consisting of Mg, Ca, Sr and Ba; x, y and z are numbers satisfying the following relationship: <x<2,0<y<1.5,0≤z<1.5。
[0040] The A component is preferably Fe, Mn and Ni, and particularly preferably Fe.
[0041] The D component is preferably Mg or Ca.
[0042] Examples of the compound having an olivine structure include lithium iron phosphate (LFP) and lithium manganese phosphate.
[0043] Furthermore, as the positive electrode active material (AM), a material whose surface is partially or entirely covered with carbon may be used in order to supplement the conductivity.
[0044] The amount of the coated carbon is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, still more preferably 5 parts by weight or less, based on 100 parts by weight of the positive electrode active material.
[0045] The compound having an olivine structure is present in the composition (C) in an amount of 70% by mass or more relative to 100% by mass of the entire positive electrode active material (AM).
[0046] More preferably, the amount is 90% by mass or more, and most preferably, the positive electrode active material (AM) is composed only of a compound having an olivine structure.
[0047] Most preferably, the positive electrode active material (AM) consists only of lithium iron phosphate (LFP).
[0048] In the positive electrode composition of the present invention, the active material (AM) has an average particle size of 1 μm or less.
[0049] The average particle size of the compound having an olivine structure is more preferably 0.01 to 0.8 μm.
[0050] The average particle size of the positive electrode active material can be measured by a particle size distribution meter for dynamic light scattering.
[0051] As the average particle size becomes smaller, the surface area becomes larger and the adhesive must be bonded with a small amount of adhesive, thus requiring the adhesive to be flexible.
[0052] By using a positive electrode active material containing a compound having an olivine structure having an average particle size of 1 μm or less, electrical characteristics such as output characteristics are excellent when the positive electrode composition for a secondary battery is used as a positive electrode of a battery.
[0053] The composition (C) of the present invention further comprises a binder (B), which comprises, preferably consists of:
[0054] a) at least one vinylidene fluoride (VDF) copolymer [polymer (F)]
[0055] b) at least one (meth)acrylic polymer [polymer (A)];
[0056] c) at least one solvent (S); and
[0057] d) Optionally at least one additive imparting conductivity.
[0058] The polymer (F) comprises repeating units derived from vinylidene fluoride (VDF) and repeating units derived from at least one hydrophilic (meth)acrylic monomer (MA) having formula (I):
[0059]
[0060] in:
[0061] - R1, R2 and R3, which are the same or different from each other, are independently selected from hydrogen atoms and C1-C3 hydrocarbon groups, and
[0062] -R X It is a C1-C 20 a hydrocarbon moiety, the functional group being selected from a hydroxyl group, a carboxyl group, an epoxy group, an ester group and an ether group,
[0063] The amount of these repeating units is from 0.05 to 10% by mole relative to the total moles of the repeating units of polymer (F).
[0064] The term "hydrophilic (meth) acrylic monomer" as used herein may comprise repeating units derived from one or more than one hydrophilic (meth) acrylic monomer (MA) as described above. In the remainder of the text, the expression "hydrophilic (meth) acrylic monomer (MA)" refers to both the plural and singular forms, i.e. they represent both one or more than one hydrophilic (meth) acrylic monomer (MA).
[0065] More preferably, the hydrophilic (meth)acrylic monomer (MA) preferably conforms to formula (II):
[0066]
[0067] wherein each of R1 and R2 has the meaning as defined above, R3 is hydrogen, and R OH is hydrogen or a C1-C5 hydrocarbon moiety containing at least one hydroxyl group and / or at least one carboxyl group; more preferably, each of R1, R2, R3 is hydrogen, and R OH Has the same meaning as detailed above.
[0068] Non-limiting examples of hydrophilic (meth)acrylic monomers (MA) are, inter alia, acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate; hydroxyethylhexyl (meth)acrylate.
[0069] The monomer (MA) is more preferably selected from:
[0070] - Hydroxyethyl acrylate (HEA) having the formula:
[0071]
[0072] - 2-Hydroxypropyl acrylate (HPA) having any of the following formulas:
[0073]
[0074] - Acrylic acid (AA) having the formula:
[0075]
[0076] - and mixtures thereof.
[0077] Most preferably, monomer (MA) is AA and / or HEA.
[0078] The polymer (F) may further contain other parts which neither affect nor impair its physicochemical properties, such as defects, terminal groups, etc.
[0079] The polymer (F) is semi-crystalline. The term semi-crystalline is intended to mean a polymer (F) having a detectable melting point. It is generally understood that a semi-crystalline polymer (F) has a heat of fusion determined according to ASTM D 3418 of advantageously at least 0.4 J / g, preferably at least 0.5 J / g, more preferably at least 1 J / g.
[0080] Polymer (F) is preferably a linear copolymer, ie it consists of macromolecules made from a substantially linear sequence of repeating units from VDF monomers and (MA) monomers; polymer (F) can thus be distinguished from graft and / or comb polymers.
[0081] The polymer (F) comprises at least 0.05 % by mole, more preferably at least 0.1 % by mole, even more preferably at least 0.2 % by mole of repeating units derived from said hydrophilic (meth)acrylic monomer (MA).
[0082] The polymer (F) comprises preferably at most 2 % by mole, more preferably at most 1.8 % by mole, even more preferably at most 1.5 % by mole of repeating units derived from said hydrophilic (meth)acrylic monomer (MA).
[0083] In a preferred embodiment of the present invention, the repeating unit derived from the hydrophilic (meth)acrylic monomer (MA) having the formula (I) is contained in the polymer (F) in an amount of 0.2 to 1 mol% relative to the total moles of the repeating units of the polymer (F).
[0084] Polymer (F) advantageously has an intrinsic viscosity measured in dimethylformamide at 25° C. greater than 0.15 l / g and at most 0.60 l / g, preferably in the range of 0.20-0.50 l / g, more preferably comprised in the range of 0.25-0.40 l / g.
[0085] The polymer (F) may further comprise recurring units derived from one or more fluorinated comonomers (CF) different from VDF.
[0086] The term "fluorinated comonomer (CF)" is intended herein to mean an ethylenically unsaturated comonomer comprising at least one fluorine atom.
[0087] Non-limiting examples of suitable fluorinated comonomers (CF) include in particular the following:
[0088] (a) C2-C8 fluoroolefins and / or perfluoroolefins, such as tetrafluoroethylene (TFE), hexafluoropropylene (HFP), pentafluoropropylene and hexafluoroisobutylene;
[0089] (b) C2-C8 hydrogenated monofluoroolefins, such as vinyl fluoride, 1,2-difluoroethylene and trifluoroethylene;
[0090] (c) having the formula CH2=CH-R f0 Perfluoroalkylethylene, where R f0 is a C1-C6 perfluoroalkyl group;
[0091] (d) Chloro- and / or brominated and / or iodinated C2-C6-fluoroolefins, such as chlorotrifluoroethylene (CTFE).
[0092] In one embodiment of the present invention, polymer (F) comprises 0.1 to 10.0 % by mole, preferably 0.3 to 5.0 % by mole, more preferably 0.5 to 3.0 % by mole of repeating units derived from said fluorinated comonomer (CF).
[0093] In a preferred embodiment of the present invention, polymer (F) comprises repeating units derived from:
[0094] at least 70% by mole, preferably at least 75% by mole, more preferably at least 85% by mole of vinylidene fluoride (VDF),
[0095] - 0.2 to 1 % by mole of a hydrophilic (meth)acrylic monomer (MA) of formula (I);
[0096] - optionally from 0.5 to 3.0% by moles of recurring units derived from at least one fluorinated comonomer (CF).
[0097] The polymer (F) can be obtained by polymerizing VDF monomers, at least one monomer (MA) and optionally at least one comonomer (CF) in suspension in an organic medium according to the procedure described, for example, in WO 2008 / 129041 or in aqueous emulsion typically as described in the art (see, for example, US 4,016,345, US 4,725,644 and US 6,479,591).
[0098] The procedure for preparing polymer (F) in suspension comprises polymerizing vinylidene fluoride (VDF) monomer, monomer (MA), and optionally comonomer (CF) in an aqueous medium in a reaction vessel in the presence of a free radical initiator, the method comprising
[0099] - continuously feeding an aqueous solution comprising the monomer (MA); and
[0100] - Maintaining the pressure in the reactor vessel above the critical pressure of vinylidene fluoride.
[0101] During the entire suspension polymerization run, the pressure is maintained above the critical pressure of vinylidene fluoride. Generally, the pressure is maintained at a value greater than 50 bar, preferably greater than 75 bar, even more preferably greater than 100 bar.
[0102] The expression "continuously feed", "continuously add" or "continuously feed" means to add the aqueous solution of the hydrophilic (meth)acrylic monomer (MA) slowly, in small amounts and incrementally until the polymerization is finished.
[0103] The polymers (F) thus obtained have a high homogeneity of the monomer (MA) distribution in the polymer backbone, which advantageously maximizes the influence of the modifying monomer (MA) on both the adhesive and / or hydrophilic behavior of the resulting copolymer.
[0104] Furthermore, the Applicant has surprisingly found that the presence of monomer (MA) homogeneously distributed in polymer (F) has the effect of improving the thermal stability of the VDF copolymer, which is otherwise unsatisfactorily low, in particular lower than the thermal stability of the VDF homopolymer.
[0105] The at least one (meth)acrylic polymer (A) different from the polymer (F) is a polymer comprising repeating units derived from at least one (meth)acryloyl monomer (MAM).
[0106] Polymer (A) can be a homopolymer or a copolymer. "Copolymer" as used herein is intended to represent a polymer with two or more different monomer units. The copolymer can be a terpolymer with three or more different monomer units or with four or more different monomer units. The copolymer can be a random copolymer, a gradient copolymer or a block copolymer formed by a controlled polymerization method. Preferably, the copolymer is formed by a free radical polymerization method or an anionic polymerization method, and the method can be any polymerization method known in the art, including but not limited to emulsion, solution, suspension polymerization, and can be carried out in batches (bulk) and semi-batch (semi-bulk).
[0107] The term (meth)acryloyl monomer (MAM) refers to a monomer having a (meth)acryloyl group in the molecule.
[0108] Suitable (meth)acryloyl monomers (MAM) are hydrophobic (meth)acryloyl monomers, which can be selected, for example, from (meth)acrylamides having the formula CH2=C(R)-C(=O)-NH-Rh, or (meth)acrylates having the formula CH2=C(R)-C(=O)-O-Rh, wherein R means hydrogen or an alkyl group having 1 to 3 carbon atoms, and Rh means a linear or branched alkyl residue having 1 to 30 carbon atoms, preferably 1 to 15 carbons, more preferably 1 to 5 carbons.
[0109] Non-limiting examples of such monomers are methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, heptyl (meth)acrylate, 2-tert-butylheptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, 5-methylundecyl (meth)acrylate, dodecyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, phenyl (meth)acrylate.
[0110] Polymer (A) may also comprise repeating units derived from at least one hydrophilic (meth)acryloyl monomer such as monoethylenically unsaturated monocarboxylic acids and derivatives. This includes in particular acrylic acid, methacrylic acid (MAA), hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxyethylhexyl (meth)acrylate, crotonic acid, 2-carboxyethyl acrylate oligomers such as B-CEA.
[0111] The expression "methyl methacrylate polymer" is used within the framework of the present invention to denote a polymer consisting of recurring units, wherein more than 50% by moles of said recurring units are derived from methyl methacrylate (MMA).
[0112] Preferred (meth)acrylic polymers (A) for use in the composition (C) of the present invention are methyl methacrylate polymers.
[0113] In a preferred embodiment of the present invention, polymer (A) is a methyl methacrylate polymer containing at least 50% by mole of methyl methacrylate monomer units, preferably at least 70% by weight, more preferably at least 80% by mole of methyl methacrylate monomer units.
[0114] According to the preferred embodiment, when polymer (A) is a copolymer, it may contain 1% to 50%, preferably 3% to 30%, and more preferably 5% to 20% by weight of at least one comonomer copolymerizable with methyl methacrylate, including but not limited to the monomer (MAM) as defined above, or other ethylenically unsaturated monomers.
[0115] The (meth)acrylic polymer (A) is prepared by polymerizing a mixture of α,β-ethylenically unsaturated (meth)acryloyl monomers (MAM), optionally in the presence of other α,β-ethylenically unsaturated monomers carrying functional groups such as carboxyl or substituted alkyl esters.
[0116] According to an embodiment of the present invention, polymer (A) may further comprise repeating units derived from one or more ethylenically unsaturated monomers [monomer (M1)], wherein the one or more ethylenically unsaturated monomers have an unsaturated heterocyclic group having at least one nitrogen atom and have the following formula (III):
[0117]
[0118] in:
[0119] R 1 is H or alkyl, wherein the alkyl is preferably methyl;
[0120] R 2 is H or alkyl;
[0121] R 3 and R 4 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms;
[0122] A is a connecting bond selected from the group consisting of:
[0123] - single covalent bonds; and
[0124] - spacer groups;
[0125] wherein X, Y and Z are independently selected from carbon atoms or nitrogen atoms;
[0126] wherein a, b and c are independently selected from integers 1 to 2;
[0127] Each dashed line represents an optional double bond.
[0128] The "unsaturated heterocyclic group having at least one nitrogen atom" in the monomer (M1) having the formula (II) preferably includes a 5- to 6-membered aromatic ring group having at least one N in the ring, and such as:
[0129]
[0130] Where * indicates the connection point of the connection key A.
[0131] Linking bond A and residue R 2 Attachment to the heterocyclic group may be at any position (on a carbon atom or a nitrogen atom).
[0132] The monomer (M1) may be, for example:
[0133] - Vinylimidazole (VIm) having the formula (IIIa):
[0134]
[0135] - 2-methyl-1-vinylimidazole having formula (IIIb)
[0136]
[0137] - 1-vinyl-1,2,4-triazole having formula (IIIc)
[0138]
[0139] - 2-vinylpyrazine having formula (IIId)
[0140]
[0141] - 4-vinylpyridine having formula (IIIe)
[0142]
[0143] - 2-vinylpyridine having formula (IIIf)
[0144]
[0145] -Hydroxy-(meth)acrylate imidazole derivatives having formula (IIIg)
[0146]
[0147] When any one of X, Y and Z in formula (III) is carbon, it may typically be the carbon of a carbonyl group.
[0148] Thus, the monomer (M1) may be, for example:
[0149] -N-vinylpyrrolidone having formula (IIIh)
[0150]
[0151] - A compound having formula (IIIi)
[0152]
[0153] The divalent spacer group A in formula (III) can typically be a group -CO-NH-(CH2) n -、-CO-O-(CH2) n or -CO-O-(CH2)n -O-CO-, but any other covalently linked group may be considered, such as a group obtained by reaction of a compound of formula (III-X):
[0154]
[0155] Where R 6 , R 8 and R 9 is as defined above,
[0156] With a compound having formula (III-Y):
[0157]
[0158] Where R 2 is as defined above, A 1 and A 2 Are two groups that react together to form a covalent bond.
[0159] For example, A 2 It can be -(CH2) m -NH2 group, wherein m is 1 to 4, preferably 2 or 3. In this case, A 1 It may be, for example, a carboxylic acid, an acid chloride, an anhydride or an epoxide.
[0160] According to another variant, A 2 It can be -(CH2) m -OH group, wherein m is 1 to 4, preferably 2 or 3. In this case, A 1 It may be, for example, a carboxylic acid, an acid chloride, an anhydride or an ester.
[0161] When the (meth)acrylic polymer (A) comprises a hydrophilic (meth)acryloyl monomer such as a monoethylenically unsaturated monocarboxylic acid, the polymer (A) may be further at least partially salified to obtain at least a portion of the acidic portion in the form of a salt.
[0162] In an embodiment of the present invention, therefore, there is provided an at least partially salified (meth)acrylic polymer (A).
[0163] Therefore, the preparation of the (meth)acrylic polymer (A) may further include a step of neutralizing at least a part of the acid group with a salt containing a monovalent cation [salt (SA)] in a suitable solvent.
[0164] The salt (SA) may be any salt capable of neutralizing the acid group, and is preferably selected from salts capable of providing alkali metal cations, tertiary ammonium or quaternary ammonium cations, more preferably capable of providing Na + , K +, Li + and or salts of quaternary ammonium cations.
[0165] The polymer (A) used in the composition (C) of the present invention preferably has a number average molecular weight (Mn) of at least 1 kDa, for example between 1 and 150 kDa. More preferably, the polymer (A) has a number average molecular weight (Mn) between 15 and 100 kDa.
[0166] The polymer (A) used in the composition (C) of the present invention preferably has a weight average molecular weight (Mw) of about 1 kDa to 150 kDa, preferably 5 kDa to 100 kDa.
[0167] In one embodiment of the present invention, polymer (A) is a methyl methacrylate polymer comprising 100 % by mole of methyl methacrylate monomer units (methyl methacrylate homopolymer).
[0168] According to another preferred embodiment, polymer (A) is a methyl methacrylate copolymer comprising at least 80% by mole of methyl methacrylate monomer units and up to 20% by mole of methacrylic acid monomer units.
[0169] The choice of solvent (S) is not particularly limited, provided that the solvent is suitable for dissolving polymer (F) and polymer (A).
[0170] The solvent (S) is typically selected from the group consisting of:
[0171] - alcohols, such as methanol, ethanol and diacetone alcohol,
[0172] - ketones, such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclohexanone and isophorone,
[0173] - linear or cyclic esters, such as isopropyl acetate, n-butyl acetate, methyl acetoacetate, dimethyl phthalate and gamma-butyrolactone,
[0174] - linear or cyclic amides, such as N,N-diethylacetamide, N,N-dimethylacetamide, dimethylformamide and N-methyl-2-pyrrolidone, and
[0175] -Dimethyl sulfoxide.
[0176] The electrode-forming composition of the present invention may further include one or more optional conductivity-imparting additives to improve the conductivity of electrodes made from the composition of the present invention.Conductivity-imparting additives for batteries are known in the art.
[0177] Examples thereof may include: carbonaceous materials such as carbon black, graphite fine powder carbon nanotubes, graphene, or fibers, or fine powder or fibers of metals such as nickel or aluminum. The optional conductive agent is preferably carbon black or carbon nanotubes.
[0178] The amount of the optional conductive agent is preferably 0% to 30% by weight relative to the total solids in the electrode forming composition. In particular, for the positive electrode forming composition, the optional conductive agent is typically 0% to 10% by weight, more preferably 0% to 5% by weight, of the total amount of solids in the composition (C).
[0179] Composition (C) may further comprise at least one wetting agent and / or at least one surfactant and one or more than one further additive.
[0180] Composition (C) may further comprise at least one non-electroactive inorganic filler material.
[0181] The term "non-electroactive inorganic filler material" is intended herein to mean a non-conductive inorganic filler material that is suitable for making an electrically insulating separator for an electrochemical cell.
[0182] The non-electroactive inorganic filler material in the separator according to the present invention typically has a resistivity (p) of at least 0.1 x 1010 ohm cm, preferably at least 0.1 x 1012 ohm cm as measured according to ASTM D 257 at 20°C.
[0183] Non-limiting examples of suitable non-electroactive inorganic filler materials include natural and synthetic silica, zeolites, alumina, titania, metal carbonates, zirconia, silicon phosphates and silicon silicates, among others.
[0184] The binder (B) used in the composition (C) according to the present invention can be prepared by any method known in the art. Suitable methods include:
[0185] - dissolving the polymer (F) with a solvent (S),
[0186] - dissolving polymer (A) with a solvent (S), preferably the solvent used to dissolve polymer (F), and
[0187] - The two solutions are mixed to provide a binder solution (B).
[0188] The weight ratio of polymer (F) to polymer (A) in binder (B) is conveniently in the range of 95:5 to 70:30. In a preferred embodiment of the present invention, the weight ratio of polymer (F) to polymer (A) in binder (B) is 90:10.
[0189] The electrode forming composition (C) can be obtained by adding and dispersing a powdered electrode material and optional additives such as an additive imparting conductivity and / or a viscosity modifier into the binder solution (B) thus obtained to obtain a uniform slurry.
[0190] The solution of polymer (F) in solvent (S) comprises in particular an amount of 5 to 20% by weight, preferably about 7 to 10% by weight, of polymer (F).
[0191] The solution of polymer (A) in solvent (S) comprises in particular an amount of 5 to 10% by weight of polymer (A) per 100 parts by weight of such solvent.
[0192] In order to obtain the binder solution (B) comprising the polymer (F) and the polymer (A) as described above in detail, it is preferred to dissolve the polymer (F) in a solvent (S) and dissolve 5 to 10% by weight of the polymer (A) in 100 parts by weight of such solvent, respectively.
[0193] In order to prepare the binder solution (B), it is preferred to dissolve the polymer (F) and the polymer (A) in the solvent (S) at a temperature of 20°C to 50°C.
[0194] Alternatively, the binder solution (B) may be prepared by first dissolving the polymer (F) in the solvent (S), and then adding the solid polymer (A) to the prepared mixture.
[0195] The total solids content (TSC) of the composition (C) of the invention is typically comprised between 15% and 70% by weight, preferably between 40% and 60% by weight, relative to the total weight of the composition (C). The total solids content of the composition (C) is understood to be the accumulation of all its non-volatile constituents, including in particular polymer (F), polymer (A), electrode active material and any solid non-volatile further additives.
[0196] When a solution of polymer (F) and a solution of polymer (A) are prepared separately and then combined with electrode active materials and optional conductive materials and other additives to prepare composition (C), an amount of solvent sufficient to produce a stable solution is used. The amount of solvent used can range from the minimum amount required to produce a stable solution to the amount required to achieve the desired total solid content in the electrode mixture after adding active electrode materials, optional conductive materials and other solid additives.
[0197] The mixing of the two solutions is carried out by any method known in the art, such as by planetary mixing followed by the dispersed phase.
[0198] The presence of polymer (A) in composition (C) makes it possible to obtain a uniform slurry composition with no signs of gelation in all preparation steps. Therefore, it is possible to use polymer (F) with polar groups in an electrode-forming composition comprising an olivine-type active material electrode and to utilize the properties of such polymers in electrodes, such as greater adhesion to the current collector, improved flexibility, and good mechanical properties.
[0199] Furthermore, polymer (A) acts as a dispersant in the binder composition and reduces the slurry viscosity compared to a composition having the same TSC but containing only polymer (F), active material and conductivity imparting additive.
[0200] Another advantage of the composition (C) of the present invention is that it is possible to provide an electrode which comprises a relatively low content by weight of binder and which makes it possible to increase the content of active material in the positive electrode in order to maximize the capacity of the battery.
[0201] The electrode-forming composition (C) of the present invention can be used in a method for producing a positive electrode [electrode (E)], the method comprising:
[0202] (i) providing a metal substrate having at least one surface;
[0203] (ii) providing an electrode-forming composition as defined above [composition (C)];
[0204] (iii) applying the composition (C) to at least one surface of a metal substrate, thereby providing a component comprising the metal substrate coated with the composition (C) on the at least one surface;
[0205] (iv) drying the assembly provided in step (iii).
[0206] The metal substrate is typically a foil, screen or mesh made of a metal such as aluminum, nickel, titanium and alloys thereof.
[0207] In step (iii) of the process of the present invention, the electrode-forming composition (C) is typically applied to at least one surface of the metal substrate by any suitable procedure such as casting, printing and roller coating.
[0208] Optionally, step (iii) may be repeated one or more times, typically by applying the electrode-forming composition (C) provided in step (ii) to the assembly provided in step (iv).
[0209] In step (iv) of the process of the invention, drying may be carried out at atmospheric pressure or under vacuum. Alternatively, drying may be carried out under a modified atmosphere, for example under an inert gas from which moisture is typically removed (water vapor content less than 0.001% v / v).
[0210] The drying temperature will be selected so as to effect removal by evaporation of the aqueous medium from the electrode (E) of the invention.
[0211] The dried assembly obtained in step (iv) may be further subjected to a compression step (such as a calendaring process) to achieve the target porosity and density of the electrode (E) of the present invention.
[0212] Preferably, the dried assembly obtained in step (iv) is subjected to hot pressing, the temperature during the pressing step being comprised between 25°C and 130°C, preferably about 60°C.
[0213] Preferred target densities of electrode (E) are comprised between 2 and 3 g / cc, preferably at least 2.1 g / cc.The density of electrode (E) is calculated as the sum of the densities of the electrode components multiplied by the products of their mass ratios in the electrode formulation.
[0214] In another aspect, the present invention relates to an electrode obtainable by the process of the present invention [electrode (E)].
[0215] Therefore, the present invention relates to an electrode (E) comprising:
[0216] - a metal substrate having at least one surface, and
[0217] - at least one layer directly adhered to at least one surface of said metal substrate, said layer consisting of a composition [composition (C')] comprising:
[0218] a) at least one positive electrode active material (AM) having an olivine structure;
[0219] b) an adhesive composition [adhesive (B')] comprising:
[0220] b') at least one polymer (F) as defined above,
[0221] b″) at least one polymer (A) as defined above;
[0222] c) Optionally, at least one additive imparting conductivity.
[0223] The composition (C') directly adhered to at least one surface of the metal substrate corresponds to the electrode forming composition (C) of the present invention, wherein the solvent has been at least partially removed during the manufacturing process of the electrode, for example in step (iv) (drying) and / or in a further compression step. Therefore, all preferred embodiments described with respect to the electrode forming composition (C) of the present invention also apply to the composition (C') directly adhered to at least one surface of the metal substrate in the electrode of the present invention, except for the aqueous medium removed during the manufacturing process.
[0224] Preferred positive electrodes (E) include:
[0225] - a metal substrate having at least one surface, and
[0226] - at least one layer directly adhered to at least one surface of said metal substrate, the at least one layer consisting of:
[0227] j) a positive electrode active material (AM) having an olivine structure in an amount of 90 to 98% by weight;
[0228] jj) a binder (B') in an amount of 0.5 to 10% by weight, preferably 1 to 5% by weight; and
[0229] jjj an additive imparting conductivity in an amount of 0.5 to 5% by weight,
[0230] wherein the above % by weight are relative to the total weight of j)+jj)+jjj).
[0231] Preferably, the positive electrode (E) comprises at least 95% by weight of active material (AM) and the electrode loading is comprised between 8 and 20 mg / cm 2 Between, preferably about 15 mg / cm 2 .
[0232] The applicant has surprisingly found that copolymers obtained by free radical polymerization of at least one phosphorus-containing unsaturated monomer with acrylic acid and / or methacrylic acid [polymer (P)] can be advantageously used as primers to provide excellent adhesion between electroactive materials and cathode current collectors.
[0233] The Applicant has surprisingly found that by using small amounts of said polymer (P) such good adhesion can be achieved that the electrochemical properties of the final electrode are not negatively affected.
[0234] Therefore, in another embodiment, the present invention relates to an electrode [electrode (E1)] comprising:
[0235] - a metal substrate having at least one surface,
[0236] a first layer adhered to said at least one surface of said metal substrate, said first layer comprising at least one polymer (P) obtained by free radical polymerization of at least one phosphorus-containing unsaturated monomer with acrylic acid and / or methacrylic acid, and
[0237] - a second layer adhered to said first layer, said second layer comprising at least the composition as defined above [composition (C')].
[0238] The metal substrate having at least one surface is preferably a surface-modified metal substrate having at least one at least partially chemically modified side.
[0239] Preferably, the polymer (P) is obtained by free radical polymerization of:
[0240] - at least one phosphorus-containing unsaturated monomer having formula (a) or (b) as shown below:
[0241] (a)
[0242]
[0243] Where n is 1 or 2;
[0244] (b) H2C=CH-P(=O)-(OH)2
[0245] With acrylic acid and / or methacrylic acid.
[0246] Preferably, polymer (P) has a molecular weight of at least 7,500 Da, more preferably from 10 kDa to 1500 kDa, even more preferably from 10 kDa to 150 kDa, especially between 10 kDa and 100 kDa.
[0247] According to a preferred embodiment, the polymer (P) is obtained by free radical copolymerization of a phosphorus-containing unsaturated monomer having the above formula (b) and acrylic acid.
[0248] According to this embodiment, the molar ratio of the phosphorus-containing unsaturated monomer having formula (b) and acrylic acid is 40:60 to 20:80, preferably 35:65 to 25:75 and even more preferably 30:70.
[0249] Preferably, according to this first embodiment, the polymer (P) has a molecular weight comprised between 25 kDa and 85 kDa.
[0250] According to another preferred embodiment, the polymer (P) is obtained by free radical copolymerization of 2-hydroxyethyl methacrylate phosphate conforming to the above formula (a) (wherein n is 1 and 2) with a mixture of acrylic acid and methacrylic acid.
[0251] More preferably, the polymer (P) is obtained by free radical copolymerization of a mixture having the following molar ratios based on the total amount of acrylic acid, methacrylic acid and 2-hydroxyethyl methacrylate phosphate having formula (a):
[0252] - acrylic acid: 65% to 90%, preferably 80% to 90%, more preferably 83%-85%,
[0253] - methacrylic acid: 5% to 30%, preferably 5% to 15%, more preferably 11%-13%,
[0254] - 2-Hydroxyethyl methacrylate phosphate: 2% to 12%, preferably 2% to 10%, more preferably 2% to 6% and even more preferably about 4%.
[0255] Preferably, according to this embodiment, the polymer (P) has a molecular weight of 15 kDa to 35 kDa.
[0256] Average molecular weight (typically weight average molecular weight) is measured by size exclusion chromatography (SEC).
[0257] Advantageously, the thickness of said first layer comprising polymer (P) is lower than 1 μm.
[0258] The electrode (E1) can be manufactured by a method comprising the following steps:
[0259] A step (1) of providing a metal substrate having at least one surface;
[0260] Optionally, a step (1b) of surface treating said at least one surface of said metal substrate to provide a surface-modified metal substrate having at least one at least partially chemically modified side surface;
[0261] a step (2) of bringing at least one polymer (P) into contact with said at least one surface of said metal substrate to provide a first layer;
[0262] A step (3) of bringing the electrode-forming composition [composition (C)] as defined above into contact with the layer obtained in the step (2).
[0263] The electrode (E) and the electrode (E1) of the present invention are particularly suitable for use in electrochemical devices, particularly secondary batteries.
[0264] The secondary battery of the present invention is preferably an alkali metal or alkaline earth metal secondary battery.
[0265] The secondary battery of the present invention is more preferably a lithium ion secondary battery.
[0266] The electrochemical device according to the present invention can be prepared by standard methods known to those skilled in the art.
[0267] Should the disclosure of any patents, patent applications, and publications incorporated by reference into this application conflict with the description of this application to the extent that it might render a term unclear, this description shall take precedence.
[0268] The present invention will now be described with reference to the following examples, which are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0269] Experimental Section
[0270] raw material
[0271] Polymer (F-1): VDF-AA (1.0% by mole) polymer having an intrinsic viscosity of 0.30 1 / g in DMF at 25°C.
[0272] HSV900: PVDF homopolymer, commercially available from Arkema.
[0273] Nano LFP: LFP P2 / C-Life C04, density: 3.34g / cm 3 , actual specific capacity: 153 mAh / g, commercially available from Johnson Matthey.
[0274] Carbon nanotubes: Orgacyl NMP 0402. 4% thin multi-walled carbon nanotubes (MWCNTs) in N-methyl-2-pyrrolidone (NMP) solvent.
[0275] AMBN: 2,2′-azobis(2-methylbutyronitrile)
[0276] Vim: Vinyl imidazole
[0277] Molecular weight determination
[0278] The mass distribution of the polymers is measured by SEC MALS analysis (SEC: Size Exclusion Chromatography - MALLS: Multi-Angle Laser Light Scattering) in order to obtain the actual values expressed in g / mol.
[0279] SEC MALLS analysis was performed with an HPLC train equipped with the following 2 detectors:
[0280] - Differential Refractometer RI-Concentration Detector
[0281] -MALLS detector (Multi-angle Laser Light Scattering) -Mass detector -Ultraviolet detector UV.
[0282] For each slice of the chromatogram (for polymer species), the software calculates:
[0283] -Polymer concentration, RI signal = constant*dn / dc*concentration
[0284] - the quality of the film Mi,
[0285] - From the specific Mi data, the software calculates the mass distribution: Mw, Mn and the polydispersity index Ip = Mw / Mn.
[0286] The calculation of the molar mass requires the refractive index increment dn / dc of the polymer. This is a constant that depends, among other things, on the nature of the mobile phase, the temperature of the experimental conditions and the wavelength of the laser.
[0287] The value "dn / dc" is calculated by the software from the mass recovery of the eluted fractions: for the polymers of the invention, dn / dc is 0.085 mL / g, yielding approximately 95 to 100% wt. mass recovery. The molar mass is calculated based on the actual Mi point without any adjustment to the log(M) curve.
[0288] The detailed analysis conditions are as follows:
[0289] Preparation 1 and 2:
[0290] - Analytical instruments: SEC system (Mini Dawn TREOS) with MALLS detector; Agilent differential refractometer (RI) and Agilent UV detector (at 254 nm)
[0291] -Pump: Agilent 1100
[0292] - Mobile phase: THF with 0.01M tetrabutylammonium tetrafluoroborate and 100 μL trifluoroacetic acid / kg eluent
[0293] - Column (manufacturer, model): Agilent Polypore (2*30cm) + guard column
[0294] - Temperature: 35℃
[0295] -Flow rate: 1.0mL / min
[0296] -Injection volume and sample concentration: 100 μL, 3 mg mL in mobile phase -1 .
[0297] Preparation 3 and 4:
[0298] Size exclusion chromatography (SEC) samples were diluted in mobile phase (THF + 0.01 M tetrabutylammonium tetrafluoroborate) and filtered (on 0.45 μm pores) prior to analysis.
[0299] The samples were analyzed by SEC equipped with a multi-angle laser light scattering (MALLS) detector according to the following conditions:
[0300] Eluent: THF + 0.01M tetrabutylammonium tetrafluoroborate
[0301] Flow rate: 1 mL min -1
[0302] Column: Agilent PL Gel 2* mixed + Guard column
[0303] Detection: RI (Agilent detector) + MALLS (TRISTAR)
[0304] Sample concentration: 0.4wt% in mobile phase
[0305] Injection volume: 100 μL
[0306] Preparation 1: Polymer (A-1): MMA homopolymer solution in DMF solution
[0307] In the 500mL three-necked round-bottom flask equipped with reflux condenser and mechanical stirrer, 15.15g (0.15mol) of MMA, 1.37g (7.12mmol) of AMBN and 123.63g of DMF were introduced at room temperature. The mixture was purged with nitrogen for 15 minutes at room temperature, and then immersed in an oil bath preheated at 80 ℃. After generally stabilizing the temperature at 75 ℃, a syringe pump was used to add 85.86g (0.86mol) of MMA to the reaction mixture in 1 hour. After the addition was completed, the reaction was stirred for another 6 hours. After this final aging step, the mixture was cooled to ambient temperature. Finally, dilution was performed to make the product a solution having a solid content of 34.61%.
[0308] Sampling 1 H NMR analysis to determine the MMA monomer conversion (CDCl3 1 HRMN):>99%
[0309] Samples were also taken for molecular weight determination: samples were diluted in mobile phase (THF + 0.01 M tetrabutylammonium tetrafluoroborate + 100 μL trifluoroacetic acid / kg eluent) and filtered (on 0.45 μm pores) prior to analysis.
[0310] result:
[0311] M n,SEC-MALLS =21,000 g·mol -1
[0312] M n,SEC-MALLS =43,000 g·mol -1
[0313]
[0314] Preparation 2: Polymer (A-2): Poly(MMA-co-MAA) copolymer solution in DMF
[0315] In a 500mL three-necked round-bottom flask equipped with a reflux condenser and a mechanical stirrer, 12.47g (0.12mol) of MMA, 2.68g (0.03mol) of MAA, 1.37g (7.34mmol) of AMBN and 123.58g of DMF were introduced at room temperature. The mixture was purged with nitrogen for 20 minutes at room temperature, and then immersed in an oil bath preheated at 80°C. After the temperature was stabilized at 75°C in general, a mixture of 70.7g (0.71mol) of MMA and 15.19g (0.18mol) of MAA was added to the reaction mixture over 1 hour using a syringe pump. After the addition was complete, the reaction was stirred for another 6 hours. After this final aging step, the mixture was cooled to ambient temperature. Finally, dilution was performed to make the product a solution with a solid content of 29.93%.
[0316] Sampling 1 H NMR analysis to determine the MMA and MAA monomer conversions:
[0317] MMA monomer conversion (CDCl3 1 H RMN):>99%
[0318] MAA monomer conversion (CDCl3 1 H RMN):>99%
[0319] Preparation 3: Polymer (A-3): Poly(MMA-co-VIm) 80:20 copolymer solution in NMP
[0320] In the 1L jacketed reactor equipped with multi-stage lighting (lightning) A320 stirring blade, reverse blade, condenser connected to micro cooler and low temperature constant temperature bath, MMA (24.537g, 0.243mol), VIm (5.766g, 0.061mol), AMBN (2.777g, 0.014mol) and 421.379g NMP were introduced at room temperature. The mixture was purged with nitrogen for 20 minutes at room temperature and under stirring, and after the nitrogen stream was left in the air, the temperature programming of the low temperature constant temperature bath was set to reach 75°C in the temperature ramp of 1 hour. At the same time, the solution of monomer MMA (139.040g, 1.375mol) and NVI (32.677g, 0.344mol) was prepared. Once the temperature in the reactor reaches 75°C, the monomer solution prepared previously was introduced in 1 hour. After the addition was completed, the reaction was aged for another 6 hours at 75°C. Then the reaction was cooled to room temperature and the reactor was unloaded.
[0321] The monomer conversion was determined by 1H NMR. The number-average molar mass and weight-average molar mass (M) of the copolymer could not be determined by size exclusion chromatography.n and M w ).
[0322] result:
[0323] MMA monomer conversion (CDCl3 1 H RMN)>99%
[0324] VIm monomer conversion (CDCl3 1 H RMN)>99%
[0325] Solid content: 30.38wt%
[0326] Preparation 4: Polymer (A-4): Poly(MMA-co-VIm) 95:5 copolymer solution in NMP
[0327] In a 1L jacketed reactor equipped with a multi-stage lighting A320 stirring blade, a reverse blade, a condenser connected to a microcooler and a low temperature constant temperature bath, MMA (28.874g, 0.286mol), VIm (1.429g, 0.015mol), AMBN (2.751g, 0.014mol) and 421.063g NMP were introduced at room temperature. The mixture was purged with nitrogen for 20 minutes at room temperature and under stirring, and after the nitrogen stream was left in the air, the temperature programming of the low temperature constant temperature bath was set to reach 75°C in a temperature ramp of 1 hour. At the same time, a solution of monomer MMA (163.622g, 1.618mol) and NVI (8.096g, 0.085mol) was prepared. Once the temperature in the reactor reaches 75°C, the previously prepared monomer solution was introduced within 1 hour. After the addition was completed, the reaction was aged for another 6 hours at 75°C. The reaction was then cooled to room temperature and the reactor was unloaded.
[0328] The monomer conversion was determined by 1H NMR. The number-average molar mass and weight-average molar mass (M) were determined by size exclusion chromatography. n and M w ).
[0329] Results and Methods:
[0330] MMA monomer conversion (CDCl3 1 H RMN)>99%
[0331] VIm monomer conversion (CDCl3 1 H RMN)>99%
[0332] M n,SEC-MALLS =35,000 g·mol -1
[0333] M n,SEC-MALLS =51,000 g·mol -1
[0334]
[0335] Solid content: 31.54wt%
[0336] Example 1:
[0337] An 8% by weight solution of polymer (F-1) in NMP was prepared.
[0338] Starting from the solution of polymer (A-1) in DMF obtained in Preparation 1 above, an 8% by weight solution of polymer (A-1) in NMP was prepared: polymer (A-1) in powder form was precipitated in distilled water from a solution in DMF, and the precipitate obtained was dried overnight in a vacuum oven at 90° C. The powder of polymer (A-1) thus obtained was dissolved in NMP at 8% by weight.
[0339] A solution of polymer (F-1) in NMP and a solution of polymer (A-1) in NMP were mixed in a 9:1 ratio (30.87 g of the solution of polymer (F-1) and 3.43 g of the solution of polymer (A-1)).
[0340] Nano-LFP (75.07 g), carbon nanotubes (14.7 g of a 4% wt solution in NMP) and an additional 15.94 g NMP were added to a solution containing polymer (F-1) and polymer (A-1) with planetary mixing followed by a dispersed phase to provide Composition 1, a cathode slurry (95.75% LFP, 0.75% carbon nanotubes and 3.5% binder) having a total solid content (TSC) of 56%.
[0341] A homogeneous slurry was obtained with no signs of gelling in all preparation steps. The results of the visual assessment of the slurry quality are summarized in Table 1.
[0342] Example 2:
[0343] An 8% by weight solution of polymer (F-1) in NMP was prepared.
[0344] An 8% by weight solution of polymer (A-2) in NMP was prepared starting from the solution of polymer (A-2) in DMF obtained in Preparation 2 above: polymer (A-2) in powder form was precipitated in distilled water and the precipitate obtained was dried overnight in a vacuum oven at 90° C. The powder of polymer (A-2) thus obtained was dissolved in NMP at 8% by weight.
[0345] A solution of polymer (F-1) in NMP and a solution of polymer (A-2) in NMP were mixed in a 9:1 ratio (30.87 g of the solution of polymer (F-1) and 3.43 g of the solution of polymer (A-2)).
[0346] Nano-LFP (75.07 g), carbon nanotubes (14.7 g of a 4% wt solution in NMP) and an additional 15.94 g NMP were added to a solution comprising polymer (F-1) and polymer (A-2) with planetary mixing followed by a dispersed phase to provide Composition 2, a cathode slurry (95.75% LFP, 0.75% carbon nanotubes and 3.5% binder) having a total solid content (TSC) of 56%.
[0347] A homogeneous slurry was obtained with no signs of gelling in all preparation steps. The results of the visual assessment of the slurry quality are summarized in Table 1.
[0348] Example 3:
[0349] An 8% by weight solution of polymer (F-1) in NMP was prepared.
[0350] Starting from the solution of polymer (A-2) in DMF obtained in Preparation 2 above, an 8% by weight solution of polymer (A-2) in NMP is prepared: polymer (A-2) in powder form is precipitated in distilled water from a solution in DMF, and the precipitate obtained is dried overnight in a vacuum oven at 90° C. The powder of polymer (A-2) thus obtained is dissolved in NMP at 8% by weight.
[0351] A solution of polymer (F-1) in NMP and a solution of polymer (A-2) in NMP were mixed in a ratio of 9:1 (13.3 g of solution of polymer (F-1) and 1.47 g of solution of polymer (A-2)).
[0352] Nano-LFP (76.64 g), carbon nanotubes (14.7 g of a 4% wt solution in NMP) and an additional 33.97 g NMP were added to a solution comprising polymer (F-1) and polymer (A-2) with planetary mixing followed by a dispersed phase to provide composition 3, i.e. a cathode slurry (97.5% LFP, 1% carbon nanotubes and 1.5% binder) having a total solid content (TSC) of 56%.
[0353] A homogeneous slurry was obtained with no signs of gelation in all preparation steps.
[0354] Example 4:
[0355] An 8% by weight solution of polymer (F-1) in NMP was prepared.
[0356] Starting from the solution of polymer (A-3) in NMP obtained in Preparation 3 above, an 8% by weight solution of polymer (A-3) in NMP was prepared.
[0357] A solution of polymer (F-1) in NMP and a solution of polymer (A-3) in NMP were mixed in a ratio of 9:1 (30.87 g of the solution of polymer (F-1) and 3.43 g of the solution of polymer (A-3)).
[0358] Nano-LFP (75.07 g), carbon nanotubes (14.7 g of a 4% wt solution in NMP) and an additional 15.94 g NMP were added to a solution containing polymer (F-1) and polymer (A-3) with planetary mixing followed by a dispersed phase to provide composition 4, i.e. a cathode slurry (95.75% LFP, 0.75% carbon nanotubes and 3.5% binder) having a total solid content (TSC) of 56%.
[0359] A homogeneous slurry was obtained with no signs of gelling in all preparation steps. The results of the visual assessment of the slurry quality are summarized in Table 1.
[0360] Example 5:
[0361] An 8% by weight solution of polymer (F-1) in NMP was prepared.
[0362] Starting from the solution of polymer (A-4) obtained in Preparation 4 above in DMF, an 8% by weight solution of polymer (A-4) in NMP was prepared.
[0363] A solution of polymer (F-1) in NMP and a solution of polymer (A-4) in NMP were mixed in a ratio of 9:1 (30.87 g of solution of polymer (F-1) and 3.43 g of solution of polymer (A-4)).
[0364] Nano-LFP (75.07 g), carbon nanotubes (14.7 g of a 4% wt solution in NMP) and an additional 15.94 g NMP were added to a solution containing polymer (F-1) and polymer (A-4) with planetary mixing followed by a dispersed phase to provide composition 5, i.e. a cathode slurry (95.75% LFP, 0.75% carbon nanotubes and 3.5% binder) having a total solid content (TSC) of 56%.
[0365] A homogeneous slurry was obtained with no signs of gelling in all preparation steps. The results of the visual assessment of the slurry quality are summarized in Table 1.
[0366] Comparative Example 1:
[0367] An 8% by weight solution of HSV900 in NMP was prepared.
[0368] Nano-LFP (75.07 g), carbon nanotubes (14.7 g of a 4% wt solution in NMP) and an additional 15.94 g NMP were added to 34.3 g of a solution containing HSV900 with planetary mixing followed by a dispersed phase to provide composition (C-1), i.e. a cathode slurry having a total solids content (TSC) of 56% and an amount of 3.5% binder.
[0369] The results of the visual assessment of the slurry quality are summarized in Table 1.
[0370] Comparative Example 2:
[0371] An 8% by weight solution of polymer (F-1) in NMP was prepared.
[0372] Nano-LFP (75.07 g), carbon nanotubes (14.7 g of a 4% wt solution in NMP) and an additional 15.94 g NMP were added to 34.3 g of a solution comprising polymer (F-1) with planetary mixing followed by a dispersed phase to provide a composition (C-2), i.e. a cathode slurry having a total solids content (TSC) of 56% and an amount of 3.5% binder.
[0373] The results of the visual assessment of the slurry quality are summarized in Table 1.
[0374] Comparative Example 3:
[0375] An 8% by weight solution of polymer (A-1) in NMP is prepared starting from the solution of polymer (A-1) in DMF obtained in Preparation 1 above: polymer (A-1) in powder form is precipitated in distilled water from a solution in DMF, and the obtained precipitate is dried in a vacuum oven at 90°C overnight.
[0376] The powder of the polymer (A-1) thus obtained was dissolved in NMP at 8% by weight.
[0377] Nano-LFP (75.07 g), carbon nanotubes (14.7 g of a 4% wt solution in NMP) and an additional 15.94 g NMP were added to 34.3 g of a solution comprising polymer (A-1) with planetary mixing followed by a dispersed phase to provide a composition (C-3), i.e. a cathode slurry having a total solids content (TSC) of 56% and an amount of 3.5% binder.
[0378] The results of the visual assessment of the slurry quality are summarized in Table 1.
[0379] Comparative Example 4:
[0380] Starting from the solution of polymer (A-2) in DMF obtained in Preparation 2 above, an 8% by weight solution of polymer (A-2) in NMP is prepared: polymer (A-2) in powder form is precipitated in distilled water from a solution in DMF, and the precipitate obtained is dried overnight in a vacuum oven at 90° C. The powder of polymer (A-2) thus obtained is dissolved in NMP at 8% by weight.
[0381] Nano-LFP (75.07 g), carbon nanotubes (14.7 g of a 4% wt solution in NMP) and an additional 15.94 g NMP were added to 34.3 g of a solution comprising polymer (A-2) with planetary mixing followed by a dispersed phase to provide a composition (C-4), i.e. a cathode slurry having a total solids content (TSC) of 56% and an amount of 3.5% binder.
[0382] The results of the visual assessment of the slurry quality are summarized in Table 1.
[0383] Table 1
[0384] Composition Slurry quality* 1 B 2 A 3 A 4 A 5 A C-1 A C-2 C C-3 B C-4 B
[0385] *A = Good: Visual appearance is homogeneous both at rest and under manual stirring. No agglomerates, phase separation, nor evidence of sediment on the container walls.
[0386] B = Moderate: The slurry appears homogeneous. There are signs of small agglomerates, such as incompletely dispersed solid particles, small gels, or thin deposits on the bottom or walls of the beaker. The slurry cannot be prevented from flowing.
[0387] C = Poor: Slurry is not homogeneous and visible signs are present. Gels or solid agglomerates are present. Slurry viscosity may be too high to allow casting and further mixing may be prevented / limited by solid agglomerate (gel-like) formation. If phase separation occurs, the viscosity of the upper and solid bottom layers is too low.
[0388] Example 6: Gelation Evaluation of Electrode-Forming Compositions
[0389] The viscosity change over time of Composition 2 and Composition (C-1) prepared as defined above was evaluated as follows.
[0390] The viscosity of the compositions at different shear rates (0.1 to 100 rad / s) and at different aging times (up to 72 hours) was evaluated by comparing the values at the same shear rate using an Anton Paar instrument with an MCR 52 plate-to-plate configuration.
[0391] The results are reported in Table 2.
[0392] Table 2
[0393]
[0394] ***Normalized relative to t0 viscosity
[0395] In view of the above, it was found that the positive electrode forming composition (C) according to the present invention is characterized by improved resistance to gelation due to the presence of the binder (B) comprising the polymer (A).
[0396] Example 7: Preparation of electrodes
[0397] By applying the electrode-forming compositions 1 to 5 and compositions (C-1) to (C-4) as described above to a 15 μm thick aluminum foil to obtain a 15 mg / cm 2 The positive electrode was obtained by drying the strip-shaped positive electrode in an oven at 90° C. to completely evaporate the solvent.
[0398] The positive electrodes thus obtained (electrodes (E1), (E2), (E4), (E5), (EC-1), (EC-2), (EC-3) and (EC-4), respectively) were visually evaluated. The results are reported in Table 3.
[0399] Table 3
[0400]
[0401]
[0402] **A = Good: Smooth appearance, no agglomerates on the dry electrode, and no signs of inhomogeneities due to bubble formation and evaporation. Easy to handle manually, the electrode has good flexibility when slightly bent and folded, and there is no sign of cracking or shedding of active material.
[0403] B = Moderate: The electrode has an average uniform appearance. Small agglomerates are detected by accurate visual inspection or optical microscopy. No material is lost and no cracks occur when gently bent.
[0404] C = Poor: Inhomogeneities on the electrode surface are visible to the naked eye (e.g., solid particles dragged during casting). Material breaks or falls off the current collector without treatment. Punching / cutting for further characterization is not possible
[0405] Example 8: Preparation of electrodes using primers
[0406] The Al current collector was etched with 5 wt. % HNO 3 solution at 40° C. for 4 minutes.
[0407] Then, it was dip-coated with a solution of polymer (P)-1, which is a random copolymer obtained by copolymerizing a mixture of acrylic acid and vinyl phosphoric acid (at a molar ratio of 70:30). Polymer (P)-1 had a weight average molecular weight (Mw) ranging from about 30 to 80 kDa as measured by GPC using the following conditions:
[0408] SEC is equipped with a multi-angle laser light scattering (MALLS) Mini Dawn TREOS detector and an Agilent concentration detector (RI detector). The SEC-MALLS system is run at a flow rate of 1 mL / min on a three-column Varian Aquagel OH mixed H, 8 μm, 3*30 cm, and has the following mobile phase: 100% water, NaCl 100 mM, NaH2PO4 25 mM, Na2HPO4 25 mM buffer (pH = 7). The polymer sample is diluted to 0.5 active wt% in the mobile phase for at least 4 hours, then filtered in a 0.45 μm microporous filter, and 100 microliters are injected into the mobile phase flow. Obtain the absolute molar mass, where the dn / dC of poly(acrylic acid) is equal to 0.1875 mL / g. As a detector, the following is used: RI (Agilent concentration detector) + MALLS (multi-angle laser light scattering) Mini Dawn TREOS.
[0409] The immersion was performed at 45° C. for 2 minutes. Then, rinsing was performed, followed by drying from room temperature to 100° C. for 5 minutes.
[0410] An appropriate amount of Composition 2 was cast on the treated Al current collector and then dried.
[0411] A positive electrode (E6) was obtained.
[0412] Positive electrode adhesion evaluation
[0413] The positive electrodes (E2), (E3) and (EC-1) were cut into strips (10 cm long and 2.5 cm wide) and applied to a rigid aluminum foil sheet with a thickness of 2 mm using a double adhesive tape measuring 2.5×8 cm, with the coated side of the electrode facing the aluminum sheet. A portion of the electrode was prevented from adhering to the tape so that one end of each strip was not in contact with the double adhesive tape, thereby pulling it out of the foil.
[0414] Each specimen was pulled from the foil at an angle of 180° using a dynamometer which allows the force required to peel the sample from the double tape to be measured. The peeling speed was 300 mm / min, T=25° C. The results are summarized in Table 4.
[0415] Table 4
[0416]
[0417] ****Normalized to EC-1
[0418] Positive electrode adhesion evaluation
[0419] The positive electrodes (E2), (E4), (E5) and (E6) were cut into strips (10 cm long and 2.5 cm wide) and applied to a rigid aluminum foil sheet of 2 mm thickness using a double adhesive tape measuring 2.5×8 cm, with the coated side of the electrode facing the aluminum sheet. A portion of the electrode was prevented from adhering to the tape so that one end of each strip was not in contact with the double adhesive tape, thereby pulling it out of the foil.
[0420] Each specimen was pulled from the foil at an angle of 180° using a dynamometer which allows the force required to peel the sample from the double tape to be measured. The peeling speed was 300 mm / min, T=25° C. The results are summarized in Table 5.
[0421] Table 5
[0422]
[0423] *****Normalized to E2
[0424] It has been demonstrated that the electrodes of the invention have improved adhesion to metal foils compared to standard electrodes of the prior art comprising PVDF.
Claims
1. A positive electrode forming composition (C), comprising at least one positive electrode active material (AM) having an olivine structure and at least one binder (B), wherein the binder (B) consists of: a) at least one vinylidene fluoride (VDF) copolymer [polymer (F)] comprising: (i) a repeating unit derived from VDF; (ii) repeating units derived from at least one hydrophilic (meth)acrylic monomer (MA) having formula (I): in: - R1, R2 and R3, which are the same or different from each other, are independently selected from hydrogen atoms and C1-C3 hydrocarbon groups, and -R X It is a C1-C 20 a hydrocarbon moiety, the functional group being selected from a hydroxyl group, a carboxyl group, an epoxy group, an ester group and an ether group, The amount of these repeating units is from 0.05% to 10% by mole relative to the total number of moles of the repeating units of polymer (F); b) at least one (meth)acrylic polymer [polymer (A)]; c) at least one solvent [solvent (S)]; and d) Optionally at least one additive imparting conductivity.
2. The composition (C) according to claim 1, wherein The hydrophilic (meth)acrylic monomer (MA) is selected from the group consisting of acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxyethylhexyl (meth)acrylate.
3. The composition (C) according to claim 1 or 2, wherein The active material (AM) has the following formula: Li x A y D z PO4, Wherein A is selected from the group consisting of Mn, Fe, Co, Ni and Cu; D is selected from the group consisting of Mg, Ca, Sr and Ba; x, y and z are numbers satisfying the following relationship: <x<2,0<y<1.5,0≤z<1.5。 4. A composition according to any one of the preceding claims, wherein The active material (AM) is lithium iron phosphate (LFP).
5. A composition (C) according to any one of the preceding claims, wherein The polymer (A) comprises repeating units derived from at least one (meth)acryloyl monomer (MAM) selected from the group consisting of a (meth)acrylamide ester having the formula CH2=C(R)-C(=O)-NH-Rh, or a (meth)acrylate ester having the formula CH2=C(R)-C(=O)-O-Rh, wherein R means hydrogen or an alkyl group having 1 to 3 carbon atoms, and Rh means a linear or branched alkyl residue having 1 to 30 carbon atoms, preferably 1 to 15 carbon atoms, more preferably 1 to 5 carbon atoms.
6. The composition (C) according to claim 5, wherein The at least one (meth)acryloyl monomer (MAM) is selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, heptyl (meth)acrylate, 2-tert-butylheptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, 5-methylundecyl (meth)acrylate, dodecyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, phenyl (meth)acrylate.
7. A composition (C) according to any one of the preceding claims, wherein The polymer (A) further comprises repeating units derived from at least one hydrophilic (meth)acryloyl monomer selected from the group consisting of acrylic acid, methacrylic acid (MAA), hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxyethylhexyl (meth)acrylate, crotonic acid, 2-carboxyethyl acrylate oligomers such as B-CEA; or a repeating unit derived from one or more ethylenically unsaturated monomers [monomer (M1)], the one or more ethylenically unsaturated monomers carrying an unsaturated heterocyclic group having at least one nitrogen atom, having the following formula (III): in: R 1 is H or alkyl, wherein the alkyl is preferably methyl; R 2 is H or alkyl; R 3 and R 4 , which are the same as or different from each other, may be selected from a hydrogen atom or a straight or branched alkyl group having 1 to 6 carbon atoms; A is a connecting bond selected from the group consisting of: - single covalent bonds; and - spacer groups; wherein X, Y and Z are independently selected from carbon atoms or nitrogen atoms; wherein a, b and c are independently selected from integers 1 to 2; Each dashed line represents an optional double bond.
8. The composition (C) according to claim 7, wherein The monomer (M1) is selected from the group consisting of: - Vinylimidazole (VIm) having the formula (IIIa): - 2-methyl-1-vinylimidazole having formula (IIIb) - 1-vinyl-1,2,4-triazole having formula (IIIc) - 2-vinylpyrazine having formula (IIId) - 4-vinylpyridine having formula (IIIe) - 2-vinylpyridine having formula (IIIf) -Hydroxy-(meth)acrylate imidazole derivatives having formula (IIIg) 9. A composition (C) according to any one of the preceding claims, wherein Polymer (A) is a methyl methacrylate polymer containing at least 50% by weight of methyl methacrylate monomer units, preferably at least 70% by weight, more preferably at least 80% by weight of methyl methacrylate monomer units.
10. The composition (C) according to claim 9, wherein The polymer (A) is a methyl methacrylate polymer comprising 100% by weight of methyl methacrylate monomer units.
11. The composition (C) according to claim 9, wherein is a methyl methacrylate polymer comprising at least 80% by weight of methyl methacrylate monomer units and up to 20% by weight of methacrylic acid monomer units.
12. The composition (C) according to any one of claims 1 to 9 or 11, wherein The polymer (A) is at least partially salified.
13. A composition (C) according to any one of the preceding claims, wherein The weight ratio of polymer (F) to polymer (A) in the binder (B) is in the range of 95:5 to 70:30, preferably 90:
10.
14. A method for manufacturing a positive electrode [electrode (E)], the method comprising: (i) providing a metal substrate having at least one surface; (ii) providing an electrode-forming composition according to any one of claims 1 to 13 [composition (C)]; (iii) applying the composition (C) provided in step (ii) to the at least one surface of the metal substrate provided in step (i), thereby providing a component including the metal substrate coated with the composition (C) on the at least one surface; (iv) drying the assembly provided in step (iii).
15. A positive electrode (E) obtainable by the method according to claim 14.
16. A positive electrode (E), comprising: - a metal substrate having at least one surface, and - at least one layer directly adhered to at least one surface of said metal substrate, the at least one layer consisting of: j) a positive electrode active material (AM) having an olivine structure in an amount of 90 to 98% by weight; jj) a binder (B') comprising b') at least one vinylidene fluoride (VDF) copolymer [polymer (F)] comprising: (i) a repeating unit derived from VDF; (ii) repeating units derived from at least one hydrophilic (meth)acrylic monomer (MA) having formula (I): in: - R1, R2 and R3, which are the same or different from each other, are independently selected from hydrogen atoms and C1-C3 hydrocarbon groups, and -R X It is a C1-C 20 a hydrocarbon moiety, the functional group being selected from a hydroxyl group, a carboxyl group, an epoxy group, an ester group and an ether group, The amount of these repeating units is from 0.05% to 10% by mole relative to the total number of moles of the repeating units of polymer (F); b″) at least one (meth)acrylic polymer [polymer (A)]; and optionally at least one additive imparting conductivity, The amount of the binder (B') is 0.5 to 10% by weight, preferably 1 to 5% by weight; and jjj) an additive imparting conductivity in an amount of 0.5 to 5% by weight, wherein the above % by weight are relative to the total weight of j)+jj)+jjj).
17. An electrochemical device comprising the electrode (E) according to claim 16.
Citation Information
Patent Citations
Electrode binder composition for lithium ion electrical storage devices
US20150280238A1
Binder containing polyvinylidene fluoride capable of fixing to a metal and associated lithium-ion battery electrode
US20180355206A1
Process for polymerizing tetrafluoroethylene in aqueous dispersion
US4016345A
Tetrafluoroethylene fine powder and preparation thereof
US4725644A
Fine powders of polytetrafluoroethylene
US6479591B2